Optimising catalyst and membrane performance and performing a fundamental analysis on the dehydrogenation of ethanol and 2-butanol in a catalytic membrane reactor - Keuler, Johan Nico (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Process Engineering))--University of Stellenbosch, 2000.